Audiological screening of high risk infants and prevalence of risk factors - M., Regina; Moideen, Sanu P.; M., Mohan; M.T.P., Mohammed; Afroze M., Khizer Hussain (International Journal of Contemporary Pediatrics, 2017)
Background: Hearing loss in early life can have deleterious effects on child’s psychosocial, scholastic and social-emotional development. Early identification and timely intervention can provide the child with better speech and language development. This study has been done to estimate the prevalence of hearing impairment among high risk infants as per Joint Committee on Infant Hearing (JCIH) criteria and to study the risk factors associated with neonatal hearing impairment. Methods: This multicentric observational study was conducted among 613 high risk infants admitted and discharged from neonatal intensive care units (NICU) of Academy of Medical Sciences, Kannur, Kerala and Sri Siddhartha Medical College and Research Centre, Tumakuru, Karnataka, India (level III neonatology units with an NICU admissions of average around 1200 per year), during the period August 2015 - August 2016 (12 months). The babies were selected based on the JCIH 2007 criteria. All babies were subjected to behavioral audiometry (BA) and Oto Acoustic Emissions (OAE), preferably within 3 weeks. Those failing OAE were reevaluated at 6th week and with Auditory brain stem response (ABR) within 3 months time. Results: A total of 613 high risk babies were screened. 42 (6.76%) among them were having hearing impairment. The most common risk factors associated with hearing impairment was NICU stay for more than 24 hours, prematurity, low birth weight and meningitis/sepsis etc. Conclusions: Hearing impairment among high risk babies is not a rare condition. In our study, the prevalence was 6.76%. Low birth weight, admission to NICU for more than 24 hours, low APGAR, meningitis/sepsis, maternal and neonatal complications are significant risk factors for hearing impairment among neonates. This highlights the need for neonatal screening. Though we recommend a universal screening program, at least a targeted approach should be practiced in neonatal care. Those babies who are found to have hearing impairment should be closely followed up with early intervention and rehabilitation.